What Is Data Governance? Understanding the Business Impact - Petrella, Andy (O'Reilly Media, Inc., 2020)
Data isn't just a commodity. It's a capital asset for driving businesses, creating value, and inspiring new ventures. Like money, data must be treated sustainably and with a serious dose of respect. Once you govern it properly and instill confidence in its quality, data can give your business a competitive advantage. In this report, data scientist and Kensu CEO Andy Petrella walks you through the data governance process. Everyone in your company needs to understand why data is so important to the business and how serious the consequences of a data breach can be. In this report, you'll learn the purpose of data governance: the discipline of creating and enforcing policies and standards to ensure that data is always treated with care and respect for safety and the law. This report helps you: Understand the basic ideas of data governance: what it is, who does it, how it fits into an organization, and what sets it apart from other kinds of assets Examine the business advantages of a well-run data governance program, including risk management, efficiency, and brand image Learn how your company's data governance program should evolve and mature over time.
Title from content provider